2019
DOI: 10.1016/j.radcr.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Rare malignant glomus tumor of the stomach with liver metastases

Abstract: We report a case of a 72-year-old male admitted in our Unit with anemia and a 10 cm liver neoplasm. Computed tomography scan showed 2 lesions respectively in the II, III and, VIII segment of the liver. Surgical resection of the larger liver mass was performed and the tumor appeared as a solid-cystic mass and a diagnosis of malignant mesenchymal tumor not otherwise specified, was made. One month later a Computed tomography scan detected a dishomogeneous gastric mass, 6 cm in diameter, in the greater curvature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 14 publications
0
31
0
3
Order By: Relevance
“…In the gastrointestinal tract, the stomach is the prevalent place for glomus tumors; however, there are only seven cases of malignant glomus tumors with metastasis in the stomach reported in the literature (Table 1). 1,4–9 The first case was reported in 2001 by Folpe et al in which the patient was a sixty-nine-year-old man with a 9.5-cm mass and liver metastasis 4. In 2002, Miettinen et al reported another patient who was also 69 years old with a 6.5-cm mass and liver metastasis 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gastrointestinal tract, the stomach is the prevalent place for glomus tumors; however, there are only seven cases of malignant glomus tumors with metastasis in the stomach reported in the literature (Table 1). 1,4–9 The first case was reported in 2001 by Folpe et al in which the patient was a sixty-nine-year-old man with a 9.5-cm mass and liver metastasis 4. In 2002, Miettinen et al reported another patient who was also 69 years old with a 6.5-cm mass and liver metastasis 5.…”
Section: Discussionmentioning
confidence: 99%
“…The next published case was introduced in 2018 by Bodolan et al In this case, the patient was an eighty-year-old woman with a mass sized 7.1 cm and liver metastasis 1. And the last published case was a seventy-two-year-old male with a mass sized 6 cm that was introduced by Toti et al’s in 2019 9. Among the aforementioned patients, only the two last cases were alive currently, and Bray et al’s patient had the most survival rate which was 72 months 7.…”
Section: Discussionmentioning
confidence: 99%
“…GGTs are deep soft tissue tumors, and the maximum tumor diameter in more than half of patients is greater than 2 cm [4,15,16]. In addition, a total of 11 patients with malignant GGTs have been reported in the literature with tumor sizes ranging from 3 to 14 cm, and 8 of the tumors were larger than 5 cm [14,4,17,7,18,19,20,21,22,23]. Therefore, a size of 5 cm might be a more appropriate indicator of risk for GGTs [4].…”
mentioning
confidence: 99%
“…Ancak mide glomus tümörleri için belirlenmiş herhangi bir kriter mevcut değildir. Literatürde mide glomus olguları genellikle benign gidişli olarak bildirilmekle birlikte, malign ya da metastatik gastrik glomus tümörü şeklinde az sayıda olgu da mevcuttur [14,15]. Bu olgulardan birinde tümör boyutu 6,5 cm ve mitoz 1-3/50 BBA izlenmiştir [9].…”
Section: Discussionunclassified